2017
DOI: 10.1016/j.mayocp.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Executive Leadership and Physician Well-being

Abstract: These are challenging times for health care executives. The health care field is experiencing unprecedented changes that threaten the survival of many health care organizations. To successfully navigate these challenges, health care executives need committed and productive physicians working in collaboration with organization leaders. Unfortunately, national studies suggest that at least 50% of US physicians are experiencing professional burnout, indicating that most executives face this challenge with a disil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
696
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,268 publications
(728 citation statements)
references
References 123 publications
22
696
0
10
Order By: Relevance
“…In pursuit of value-alignment, some organizations incorporate physician's perspectives though physicianadministrator dyad leadership structures, collaborative distributive leadership styles, and leadership traits to engage and empower, seek input, get buy-in, recognize, and inspire; these are reported to improve professional satisfaction and reduce burnout. (Eisenberg & Williams, 1981;Hemker & Solomon, 2016;Oostra, 2016;Shanafelt, Gorringe, et al, 2015;Shanafelt & Noseworthy, 2017;Swensen, Kabcenell, & Shanafelt, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pursuit of value-alignment, some organizations incorporate physician's perspectives though physicianadministrator dyad leadership structures, collaborative distributive leadership styles, and leadership traits to engage and empower, seek input, get buy-in, recognize, and inspire; these are reported to improve professional satisfaction and reduce burnout. (Eisenberg & Williams, 1981;Hemker & Solomon, 2016;Oostra, 2016;Shanafelt, Gorringe, et al, 2015;Shanafelt & Noseworthy, 2017;Swensen, Kabcenell, & Shanafelt, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Burned out physicians may withdraw from work physically or emotionally, which has adverse effects on providing affordable access to safe high-quality health care. As such, physician burnout is described as a public health crisis (Noseworthy et al, 2017) and physician wellbeing is described as the missing quality indicator of health system performance (Bodenheimer & Sinsky, 2014;Olson, 2017;Wallace, Lemaire, & Ghali, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The Mayo Clinic Physician Wellbeing Program, for example, has demonstrated that modifications to the workplace, especially around time, can increase physician wellbeing. 27 However, such structural interventions may not be a panacea. Studies of the 2011 duty hour reforms have demonstrated that working less may not decrease depressive symptoms, increase the number of hours slept, or improve wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…They are beyond the scope of this article. Addressing various systemic institutional factors is an important overall strategy . One important matter that can be tackled at the departmental level would be to provide good clinical leadership.…”
Section: Four Conceptual Domains Of Healthmentioning
confidence: 99%